Changes in the Lipid Metabolism of the Longissimus thoracis Muscle in Bulls when using Different Feeding Strategies during the Growing and Finishing Phases - Torrecilhas, Juliana Akamine [UNESP]; Pereira, Guilherme Luis [UNESP]; Vito, Elias San; Fiorentini, Giovani; Ramirez-Zamudio, Germán Darío; Fonseca, Larissa Simielli [UNESP]; Torres, Rodrigo de Nazaré Santos [UNESP]; Simioni, Tiago Adriano [UNESP]; Duarte, Juliana Messana [UNESP]; Machado Neto, Otavio Rodrigues [UNESP]; Curi, Rogério Abdallah [UNESP]; Chardulo, Luis Artur Loyola [UNESP]; et al. (MDPI, 2023)
The objective was to evaluate the supplementation strategy’s effect on beef cattle during the growing phase and two systems during the finishing phase. One hundred and twenty young bulls were randomly divided in a 2 × 2 factorial design to receive either mineral (ad libitum) or protein + energy (3 g/kg body weight (BW)/day) during the growing phase and pasture plus concentrate supplementation (20 g/kg BW/day) or feedlot (25:75% corn silage:concentrate) during the finishing phase. Feedlot-fed bulls had meat (Longissimus thoracis—LT) with a higher content of lipids and saturated and monounsaturated fatty acids and a greater upregulation of stearoyl-CoA desaturase and sterol regulatory element-binding protein-1c than animals that fed on pasture (p < 0.05). On the other hand, pasture-fed bulls had meat with a higher content of α-linoleic acid, linolenic acid, and n6 and a greater n6:n3 ratio compared to the feedlot-fed group (p < 0.05). In addition, meat from pasture-fed bulls during the finishing phase had 17.6% more isocitrate dehydrogenase enzyme concentration than the feedlot group (p = 0.02). Mineral-fed and pasture-finished bulls showed down-regulation of peroxisome proliferator-activated receptor gamma (p < 0.05), while the bulls fed protein + energy and finished in the feedlot had higher carnitine palmitoyltransferase 2 expression (p ≤ 0.013). In conclusion, mineral or protein + energy supplementation in the growing does not affect the fatty acid composition of intramuscular fat of LT muscle. In the finishing phase, feeding bulls in the feedlot upregulates the lipogenic genes and consequently improves the intramuscular fat content in the meat.
Keywords: beef cattle; lipogenic genes; marbling; meat quality